Proposals for Upper Limits of Safe Intake for Methionine, Histidine, and Lysine in Healthy Humans. (1st October 2020) - Cynober, Luc; Bier, Dennis M; Stover, Patrick; Kadowaki, Motoni; Morris, Sidney M; Elango, Rajavel; Smriga, Miro
ABSTRACT: Based on research presented during the 10th Amino Acid Assessment Workshop, no observed adverse effect levels (NOAELs) for supplemental methionine at 46 mg/(kg·d) (∼3.2 g/d), for supplemental histidine at 8.0 g/d, and for supplemental lysine at 6.0 g/d have been proposed. These NOAELs are relevant to healthy adults and are applicable only to high-purity amino acids administered in fortified foods or dietary supplements. Because individuals are exposed to the above supplemental amino acids in the context of complex combinations of essential amino acids or individually in dietary supplements for various physiologic benefits, such as body fat reduction, skin conditioning, mental energy increase, or herpes simplex treatments, the above safety recommendations will make an important contribution to regulatory and nutritional practices.